Female Genital Mutilation/Cutting Resulting in Genital Tract Obstruction and Sexual Dysfunction: A Case Report and Literature Review - Anwar Sadat Seidu; Haruna Danamiji Osman; Kingsley Appiah Bimpong; Kwame Afriyie (Case Reports in Obstetrics and Gynecology)
Female Genital Mutilation/Cutting (FGM/C) is the practice of cutting parts of the female external genitalia in fulfillment of sociocultural obligations and in some cases for nonmedical reasons. It is classified into 4 main types depending on the extent of cutting. Some forms of FGM/C are common in at least 29 countries globally, mainly in Africa. The overall prevalence of FGM/C in Ghana is approximately 4%. The motivation for this practice varies from community to community but includes the fulfillment of cultural values, uplifting the girl child, and, according to some reports, reducing sexual desire and promiscuity. The objective of this article is to illustrate how FGM/C resulted in sexual dysfunction in a young woman married for 2 years. We present a 19-year-old female who was subjected to female genital cutting in her formative years who presented with apareunia for 2 years in her marriage. We illustrated how FGM/C led to a genital tract obstruction with resultant sexual dysfunction. Examination revealed a Type 3 FGM/C (infibulation) with almost complete occlusion of the genital tract. She underwent a successful defibulation and resumed sexual activity with her husband within 6 weeks of the procedure.